Non-catalytic transesterification of dry microalgae to fatty acid ethyl esters using supercritical ethanol and ethyl acetate. (1st September 2020) - Mani Rathnam, V.; Modak, Jayant M.; Madras, Giridhar
Graphical abstract: Highlights: Biodiesel was synthesized from microalgae. Non-catalytic transesterification was performed with two supercritical fluids. Rate constants were determined based on pseudo first order kinetic model. Activation energies were obtained from temperature dependence of the rate constants. Reaction rates were faster in ethanol compared to ethyl acetate. Abstract: The decline of fossil fuel reserves and the problems of climate change due to emission of greenhouse gases necessitates the need for alternative sustainable green biofuels. Biodiesel is one such green biofuel which is a mixtures of mono-alkyl esters. In the present study, fatty acid ethyl esters were synthesized from dry microalgae in supercritical ethanol and ethyl acetate. The temperature was varied from 523 to 653 K while keeping pressure at 20 MPa and the ratio of algae to ethylating agent (wt./vol.) at 1:10. The duration of the transesterification reaction was between 20 and 60 min and 20 to 80 min for the ethanol and ethyl acetate systems, respectively. For the ethanol system, >95% of conversions were obtained in 50 min at 593 K whereas with the ethyl acetate system, >60% of conversions were obtained in 50 min at 653 K. The rate constants and activation energies were evaluated by pseudo first order kinetics and Arrhenius equation, respectively. The activation energies were 67.1 and 78.5 kJ/mol for ethanol and ethyl acetate systems, respectively. The reaction rates were higher for ethanol compared to ethyl acetate system.